Humanitarian Intervention in International and Islamic Law (American Journal of Islam and Society, 2003)
In this paper, I look into the moral foundation of humanitarian intervention in international law and its Islamic counterpart. My objective is to identify the traits shared by both sets of laws, and to see if the same or similar justification can be used across cultures to reach the same goal. In other words, one goal is to assess the claims that the basis upon which humanitarian intervention is justified has a universal appeal. Both international and Islamic law justify humanitarian intervention on moral grounds. International law bases its justification upon the human rights discourse. Islamic law provides enough bases for legitimizing humanitarian intervention, and Qur’anic verses, scholarly opinions, and Islamic principles provide a sound background for it. Paramount in this task is the concept of human dignity (karamah al-insan). We found no disagreement on this fundamental issue between the Universal Declaration of Human Rights (UDHR) and Islamic law. Human dignity, as understood in international human rights and its Islamic counterpart, thus could form the jus cogens of international law, a common human heritage upon which everybody can agree.